Somatostatin Receptors and Analogs in Pheochromocytoma and Paraganglioma: Old Players in a New Precision Medicine World - Patel, Mayank; Tena, Isabel; Jha, Abhishek; Taieb, David; Pacak, Karel (Frontiers in Endocrinology, 2021)
Neuroendocrine tumors overexpress somatostatin receptors, which serve as important and unique therapeutic targets for well-differentiated advanced disease. This overexpression is a well-established finding in gastroenteropancreatic neuroendocrine tumors which has guided new medical therapies in the administration of somatostatin analogs, both ‘cold’, particularly octreotide and lanreotide, and ‘hot’ analogs, chelated to radiolabeled isotopes. The binding of these analogs to somatostatin receptors effectively suppresses excess hormone secretion and tumor cell proliferation, leading to stabilization, and in some cases, tumor shrinkage. Radioisotope-labeled somatostatin analogs are utilized for both tumor localization and peptide radionuclide therapy, with 68Ga-DOTATATE and 177Lu-DOTATATE respectively. Benign and malignant pheochromocytomas and paragangliomas also overexpress somatostatin receptors, irrespective of embryological origin. The pattern of somatostatin receptor overexpression is more prominent in succinate dehydrogenase subunit B gene mutation, which is more aggressive than other subgroups of this disease. While the Food and Drug Administration has approved the use of 68Ga-DOTATATE as a radiopharmaceutical for somatostatin receptor imaging, the use of its radiotherapeutic counterpart still needs approval beyond gastroenteropancreatic neuroendocrine tumors. Thus, patients with pheochromocytoma and paraganglioma, especially those with inoperable or metastatic diseases, depend on the clinical trials of somatostatin analogs. The review summarizes the advances in the utilization of somatostatin receptor for diagnostic and therapeutic approaches in the neuroendocrine tumor subset of pheochromocytoma and paraganglioma; we hope to provide a positive perspective in using these receptors as targets for treatment in this rare condition.